2017
DOI: 10.1038/s41598-017-03118-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-step ATP-driven opening of cohesin head

Abstract: The cohesin ring is a protein complex composed of four core subunits: Smc1A, Smc3, Rad21 and Stag1/2. It is involved in chromosome segregation, DNA repair, chromatin organization and transcription regulation. Opening of the ring occurs at the “head” structure, formed of the ATPase domains of Smc1A and Smc3 and Rad21. We investigate the mechanisms of the cohesin ring opening using techniques of free molecular dynamics (MD), steered MD and quantum mechanics/molecular mechanics MD (QM/MM MD). The study allows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 73 publications
(144 reference statements)
0
28
0
Order By: Relevance
“…The interaction between RAD21 and STAG1/2 is crucial for the proper functioning of the cohesin complex (Guacci et al 2019), and both impairing (Ser345Pro) or over-stabilizing (Pro367Arg) variants within the RAD21-STAG domain are predicted to cause dysfunction of the complex, presumably through affecting the continuous cycle of formation and disengagement of the cohesin ring (Marcos-Alcalde et al 2017).…”
Section: Rad21 Missense Variants and Their Predicted Effect On Proteimentioning
confidence: 99%
“…The interaction between RAD21 and STAG1/2 is crucial for the proper functioning of the cohesin complex (Guacci et al 2019), and both impairing (Ser345Pro) or over-stabilizing (Pro367Arg) variants within the RAD21-STAG domain are predicted to cause dysfunction of the complex, presumably through affecting the continuous cycle of formation and disengagement of the cohesin ring (Marcos-Alcalde et al 2017).…”
Section: Rad21 Missense Variants and Their Predicted Effect On Proteimentioning
confidence: 99%
“…In prokaryotic condensin, the binding of ScpA to SMC dimers presumably forces the head domains into different configurations, owing to their association with opposite ends of the kleisin subunit. ATP binding or hydrolysis might trigger distinct conformational changes into the two head domains that could act synergistically to open the tripartite ring for DNA entry (26). Despite all of this fragmentary evidence, how the opening of the ring is achieved is not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…This general structure is formed in both prokaryotic and eukaryotic SMC-kleisin complexes, suggesting that asymmetric ring formation is a universal feature (3,39). A recent study suggested evidence that the ATP-dependent head-head engagement induces a lever movement of the SMC neck region, which might help to separate the coiled-coil arms (22,26).…”
Section: Coevolutionary Information Suggests Condensin As a Single Ringmentioning
confidence: 96%
See 2 more Smart Citations